Modulation of adenosine receptor affinity and intrinsic efficacy in adenine nucleosides substituted at the 2-position - Ohno, Michihiro (2004)
We studied the structural determinants of binding affinity and efficacy of adenosine receptor (AR) agonists. Substituents at the 2-position of adenosine were combined with N(6)-substitutions known to enhance human A(3)AR affinity. Selectivity of binding of the analogues and their functional effects on cAMP production were studied using recombinant human A(1), A(2A), A(2B), and A(3)ARs. Mainly sterically small substituents at the 2-position modulated both the affinity and intrinsic efficacy at all subtypes. The 2-cyano group decreased hA(3)AR affinity and efficacy in the cases of N(6)-(3-iodobenzyl) and N(6)-(trans-2-phenyl-1-cyclopropyl), for which a full A(3)AR agonist was converted into a selective antagonist; the 2-cyano-N(6)-methyl analogue was a full A(3)AR agonist. The combination of N(6)-benzyl and various 2-substitutions (chloro, trifluoromethyl, and cyano) resulted in reduced efficacy at the A(1)AR. The environment surrounding the 2-position within the putative A(3)AR binding site was explored using rhodopsin-based homology modeling and ligand docking.